2015
DOI: 10.1111/tbed.12328
|View full text |Cite
|
Sign up to set email alerts
|

How to Assess Data Availability, Accessibility and Format for Risk Analysis?

Abstract: Risk assessments are mostly carried out based on available data, which do not reflect all data theoretically required by experts to answer them. This study aimed at developing a methodology to assess data availability, accessibility and format, based on a scoring system and focusing on two diseases: Venezuelan equine encephalomyelitis (VEE), still exotic to Europe, and alveolar echinococcosis, caused by Echinococcus multilocularis (EM), endemic in several Member States (MSs). After reviewing 36 opinions of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 13 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…Therefore, although there is accessibility to certain data (e.g. by officially demanding access to international organizations) limitations in access is still high as stated in previous studies (Bellet et al, 2012;Humblet et al, 2016). Moreover, current existing databases for animal health data have not always been designed with the potential for exchange of data and accessibility to a variety of stakeholders (Humblet et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, although there is accessibility to certain data (e.g. by officially demanding access to international organizations) limitations in access is still high as stated in previous studies (Bellet et al, 2012;Humblet et al, 2016). Moreover, current existing databases for animal health data have not always been designed with the potential for exchange of data and accessibility to a variety of stakeholders (Humblet et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…Data in animal health systems are crucial for epidemiological analysis and even if it is evident that there have been advances in collecting data and improvement in animal health systems (FAO, 2011; OIE, 2017), there is yet a strong need for improving data availability and accessibility; not only for decision makers but also for research scientists (Humblet et al. 2016). This is reflected in the results of this survey which showed that for the respondents, the overall main issue and constraint they indicated was in fact data accessibility and availability.…”
Section: Discussionmentioning
confidence: 99%
“…Although, there is accessibility to certain data (e.g. by officially demanding access to international organizations) respondents showed that access to databases on public and animal health, access limitation are still high (Bellet et al, 2012;EFSA, 2020;Humblet et al, 2016). Additionally this access can be hindered by the limited knowledge of computer science (translating PDF or HTLM format to EXCEL or text using text mining) or heavy manual work required by the conversion as stated by Humblet et al (2016).…”
Section: Discussionmentioning
confidence: 99%
“…Preferred forms of data where Excel and PDF, but as stated by Humblet et al (2016), the main forms of data they found were PDF and HTLM files. Although raw tabulated data (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation